International Financial Statistics Yearbook, 2006. (International Financial Statistics; International Financial Statistics ;, 2006)
The International Financial Statistics Yearbook, usually published in September, contains available annual data covering 12 years for countries appearing in the monthly issues of IFS. The IFS service is the standard source of international financial statistics. Additional time series in country tables and some additional tables of area and world aggregates are included in the Yearbook.